ON THE FORMS AND THORNS OF LINGUISTIC INDETERMINACY IN CHINESE LAW - Mannoni, Michele (Comparative Legilinguistics, 2021)
This study addresses the different types and implications of linguistic indeterminacy in Chinese law. It firstly draws on the studies of scholars of different disciplines, such as linguistics and philosophy of language, to provide a taxonomy of indeterminacy in language. It then provides examples of each type, highlighting the implications in law and legal interpretation. It uses linguistic data from various texts, such as statutory laws and judgements, and analyse them with various methods, including discourse analysis and corpus linguistics. This study argues that when the language of the law is indeterminate, the legal outcomes may be particularly uncertain. It suggests that although it is difficult to ascertain whether the degree of indeterminacy is higher in some languages more than in others, some linguistic mechanisms at the word-formation level in Chinese are remarkably ambiguous. When uncertain terms are in key parts of the law, the consequences may be more serious. The study of linguistic indeterminacy in Chinese has implications for the study of forensic linguistics, and Chinese studies in general.